Evaluation of silk‐based bioink during pre and post 3D bioprinting: A review. Issue 2 (31st August 2020) - Gupta, Sharda; Alrabaiah, Hussam; Christophe, Marquette; Rahimi‐Gorji, Mohammad; Nadeem, Sohail; Bit, Arindam
Abstract: During past few decades, the demand for the replacement of damaged organs is increasing consistently. This is due to the advancement in tissue engineering, which opens the possibility of regeneration of damaged organs or tissues into functional parts with the help of 3D bioprinting. Bioprinting technology presents an excellent potential to develop complex structures with precise control over cell suspension and structure. A brief description of different types of 3D bioprinting techniques, including inkjet‐based, laser‐based, and extrusion‐based bioprinting is presented here. Due to innate advantageous features like tunable biodegradability, biocompatibility, elasticity and mechanical robustness, silk has carved a niche in the realm of tissue engineering. In this review article, the focus is to highlight the possible approach of exploring silk as bioink for fabrication of bioprinted implants using 3D bioprinting. This review discusses different type of degumming, dissolution techniques for extraction of proteins from different sources of silk. Different recently reported 3D bioprinting techniques suitable for silk‐based bioink are further elaborated. Postprinting characterization of resultant scaffolds are also describe here. However, there is an astounding progress in 3D bioprinting technology, still there is a need to develop further the current bioprinting technology to make it suitable for generation of heterogeneous tissue construct. The possibility of utilizing the adhesive property of sericin to consider it as bioink is elaborated.